APPLYING MULTIREPRESENTATION BASED PHYSICS LEARNING TO IMPROVE THE ABILITY OF REPRESENTATION OF STUDENTS IN CLASS X MIPA2 SMA BABUSSALAM PEKANBARU - Winda Muzdalifah; Mitri Irianti; Maimurni Maimurni (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2018)
This study aims to improve students’ representation skills by applying multirepresentation based physics learning in Class X MIPA2 SMA Babussalam Pekanbaru. This classroom action research is conducted with two cycles where one cycle step consist of planning, implementation of observation and reflection. The subjects of the study were students of class X MIPA2 as many as 33 female students. The data collection instrument is a test of representation ability given to the student at the end of each cycle. The technique of data analysis is descriptive with result of data analysis showed: the ability of representation of students based on the aspect of representation ability increased by 13,69%, while the ability to present representation into four format (graph, image, mathematical and verbal) increased by 10,11%. Thus, it can be concluded that the aplication of physics learning with multirepresentation based can improve the ability of representation of students of Class X MIPA2 SMA Babussalam Pekanbaru.